The Impact of Government Policy Regarding Waste Management in Tapin Districts South Kalimantan Province - Magriaty, Riry; Murtilaksono, Kukuh; Anwar, Syaiful (Jurnal Bina Praja, 2020)
The support of the local government and all social levels in the community is the key to successful waste management systems. Waste is mainly produced by community households. Deficient treatment and disposal severely pollute the environment. Therefore, the community must have an active role in protecting the environment. Regulation is an important aspect of policies and programs for the implementation of the waste management system to ensure that lower regulation is in line with the higher policies made by the central government. The objective of the study was to review regional regulation on waste management, comparing them to the central regulation government of waste policy, and analyze the implementation of the waste management system in the region. Content analysis was used to analyze the waste management of regional government policy. The implementation of waste management systems was analyzed using primary data obtained through observation. The secondary data was obtained by classifying the waste generation in tabular data calculated from the average of waste production by household per capita to the number of the population each subdistrict. The result indicated that the Regulation of Tapin District No. 6 of 2015 on the waste management system is in line with the central government waste policy. The implementation of waste management systems had not been carried out effectively by the regional government. The district generated solid waste at 93.3 tons each day and can only manage 27.21% in 4 subdistricts of urban settlement areas. The solid waste generation can be classified into five classes. Most are in the low and very low waste generation class. The very high generation class was in subdistricts, which have the highest population density in the region.